Type specimens of Primates (Mammalia) in the collections of the Museum für Naturkunde Berlin - Turni, Hendrik (Zootaxa, 2024)
The present catalog documents all the primate type specimens held at the collection of the Museum für Naturkunde Berlin [MfN]. Due to insufficient labeling at the time of receipt and description, many types remained unrecognized, labeled with synonymous or incorrect names until now. For identification of all types, including the previously unrecognized type specimens, approximately 8,000 primate specimens were revised in the MfN collection, 144 of them represent primary types (holotypes, lectotypes, and syntypes) and 141 paratypes or paralectotypes could be found. These types belong to 129 described primate species and subspecies, of which 44 are currently in use.